设f(x)为连续型随机变量X的密度函数,则对任意的aA: [img=92x39]1802e2aa01c2150.jpg[/img]
B: [img=81x40]1802e2aa0b123c6.jpg[/img]
C: [img=70x40]1802e2aa139d6a9.jpg[/img]
D: [img=99x48]1802e2aa1bc0ab9.png[/img]
B: [img=81x40]1802e2aa0b123c6.jpg[/img]
C: [img=70x40]1802e2aa139d6a9.jpg[/img]
D: [img=99x48]1802e2aa1bc0ab9.png[/img]
A
举一反三
- 设连续型随机变量X的分布函数为[img=236x94]180387de4fc1611.png[/img]则E(X) = ( ). A: 0 B: 1 C: 2 D: 3
- 设连续型随机变量X的分布函数为[img=236x94]1802f2bbd2ea28b.png[/img]则E(X) = ( ). A: 0 B: 1 C: 2 D: 3
- 设连续型随机变量X的分布函数为[img=236x94]18031e9684e0649.png[/img]则E(X) = ( ). A: 0 B: 1 C: 2 D: 3
- 设连续型随机变量X的分布函数为[img=236x94]1802fe36702529e.png[/img]则E(X) = ( ). A: 0 B: 1 C: 2 D: 3
- 设连续型随机变量X的分布函数为[img=236x94]1803a74dc4a70b4.png[/img]则E(X) = ( ). A: 0 B: 1 C: 2 D: 3
内容
- 0
设连续型随机变量X的分布函数为[img=236x94]1802e8d4e6f83a3.png[/img]则E(X) = ( ). A: 0 B: 1 C: 2 D: 3
- 1
设连续型随机变量X的分布函数为[img=236x94]1803395e7f08938.png[/img]则E(X) = ( ). A: 0 B: 1 C: 2 D: 3
- 2
设连续型随机变量X的分布函数为[img=236x94]1802f28fadcff87.png[/img]则E(X) = ( ). A: 0 B: 1 C: 2 D: 3
- 3
设连续型随机变量X的分布函数为[img=236x94]1803c07b7cca5b7.png[/img]则E(X) = ( ). A: 0 B: 1 C: 2 D: 3
- 4
设连续型随机变量X的分布函数为[img=236x94]1802f2bee9e3cf6.png[/img]则E(X) = ( ). A: 0 B: 1 C: 2 D: 3